ANTARA PEREMPUAN, ISLAM, DAN TANI (Studi Kasus di Dusun Kelambi Desa Pandan Indah Kecamatan Praya Barat Daya Kabupaten Lombok Tengah) - Rohimi Rohimi; Ali Akhbar Abaib Mas Rabbani Lubis (PSGA LP2M IAIN Pontianak, 2020)
This paper discusses women who are considered incomplete as humans, inferiorly, may only play a role in the domestic (household) room. So the researches focused on discussing women, Islam, and farmers in Dusun Kelambi, Desa Pandan Indah, Kabupaten Praya Barat Daya, Kabupaten Lombok Tengah to test these assumptions. The aim is to answer the urgency of women farmers involved in public activities and the role of farmworkers in Dusun Kelambi, Desa Pandan Indah. This research is included in the cluster of qualitative research by involving the library research approach and fieldwork, answering the question in the perspective of the maqasid syari’ah. The result showed that farmer women in Dusun Kelambi did farm work based on equity and necessity considerations, including family food security (hifz al-nafs wa al-mal), continuing their children’s schooling (hifz al’aql wa nasl), and of course the entire population is Muslim (hifz al-din).